1999
DOI: 10.1037/0012-1649.35.3.811
|View full text |Cite
|
Sign up to set email alerts
|

Emotional availability and attachment representations in kibbutz infants and their mothers.

Abstract: Three components of the attachment transmission model were examined in 48 kibbutz dyads from 2 kibbutz sleeping arrangements: communal and home-based. Concurrent assessments used the Strange Situation procedure (M. D. Ainsworth, M. C. Blehar, E. Waters, & S. Wall, 1978) for infants' attachment relations, the Adult Attachment Interview (C. George, N. Kaplan, & M. Main, 1985) for mothers' attachment representations, and the Emotional Availability Scales (Z. Biringen, J. L. Robinson, & R. N. Emde, 1993) for emoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
2
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(74 citation statements)
references
References 49 publications
7
64
2
1
Order By: Relevance
“…Quality of the parent-child relationship was assessed with the Emotional Availability Scales (EAS, third edition, Biringen, Robinson, & Emde, 1998). The EAS are related to the security of the parentchild attachment relationship, as well as to other aspects of the parent-child relationship, like maternal affect and the mother's representations of the child (Aviezer, Sagi, Joels, & Ziv, 1999;Biringen, 2000). Various studies demonstrated construct validity for this measure (Biringen, 2000), and the EAS is proven to be highly stable (Riksen-Walraven, Smeekens, & Stapert, 1999).…”
Section: Methodsmentioning
confidence: 99%
“…Quality of the parent-child relationship was assessed with the Emotional Availability Scales (EAS, third edition, Biringen, Robinson, & Emde, 1998). The EAS are related to the security of the parentchild attachment relationship, as well as to other aspects of the parent-child relationship, like maternal affect and the mother's representations of the child (Aviezer, Sagi, Joels, & Ziv, 1999;Biringen, 2000). Various studies demonstrated construct validity for this measure (Biringen, 2000), and the EAS is proven to be highly stable (Riksen-Walraven, Smeekens, & Stapert, 1999).…”
Section: Methodsmentioning
confidence: 99%
“…As a consequence, parent-child interaction not only serves as a key determinant for children's socioemotional adaptation (Emde & Easterbrooks, 1985), it also represents a principal setting for the acquisition of language and for the expansion of other cognitive abilities (Greenspan, 1997;Rogoff & Gardner;Vygotsky, 1978). Among the prominent factors that lead to effective parent-child interaction, emotional availability is crucial (Aviezer, Sagi, Joels, & Ziv, 1999;Biringen & Robinson, 1991;Bretherton, 2000). Emotional availability (EA; Biringen, 2000) is a relationship construct that refers to the quality of emotional exchanges between parents and their children, focusing on the two partners' accessibility to each other and their ability to read and respond appropriately to one another's communications (Biringen & Robinson).…”
Section: Parent-child Interaction and Dyadic Emotional Availabilitymentioning
confidence: 99%
“…Based on the attachment theoretical assumption that the quality of a child's experiences with his caregiver affects his development [2,3], maternal EA has been shown to be related to diverse domains of child development. In particular, maternal EA has been linked to child attachment security [4,5,6]. Moreover, longitudinal studies have shown that high EA predicts better emotion regulation [7], lower rates of psychopathological symptoms [6,8], higher social competence [9], better language skills and general mental development [10], and better theory of mind (ToM) skills in children [11].…”
Section: Introductionmentioning
confidence: 99%